Correlation between Milk Yield, Somatic Cell Count and Milk Quality in Dairy Farming - Kaygısız, Ferhan; Çiftçioğlu, Gürhan; Türkay, Gülhan H; Cevger, Yavuz; Issa, Ghassan; Yalçıntan, Hülya; Yardibi, Hasret (Animal Review, 2015)
This study investigated between milk yield and Somatic Cell Count, sampled from 3 different dairy enterprises. Chemical and microbiological parameters analyzed for the relation with milk yield. Milk samples have been collected from 10 dairy cows, two times per month during 1 year period. Bacteriological analyzes have been employed for milks. Milk yield data for each cow have been recorded in every sampling day. Depending on the logistic regretion analyses on the data collected from all enterprises; high total plate count and E.coli counts have negative effects on milk yield, but has been found significally important (p<0.05) only for the data of E.coli. counts. In group 1; somatic cell count and E.coli counts have negative effect on milk yield and only the data of E.coli has been found statistically important (p<0.05). In group 2; only the data related negative effect of E.coli counts on milk yield has been found as statistically important (p<0.05). The third group, total plate count has negative effect on milk yield. Regarding to the chemical analyses of fat in milk, non-fat dry matter, density and protein values have been detected in the enterprises 1, 2 and 3 as 2.88, 3.56, 4.34; 7.91, 7.83, 8.12; 1026.4, 1025.8, 1026; 3.04, 2.96, 3.07, respectively. According to the correlation analyses applied between milk yield and fat in milk, non fat-dry matter, protein and density in milk in all enterprises; there were significant correlation between non-fat dry matter and milk yield in enterprise 2 (p<0.05) and density and milk yield in enterprise 3 (p<0.01).